Design and Cost Estimation of Modern Angkringan Cart - Darwin Yuwono Riyanto; Hardman Budiarjo; Mochamad Farkhan Syahtoni; Martinus Sony Erstiawan (Meraki: Journal of Creative Industries, 2025)
This research aims to develop an angkringan cart design derived from traditional angkringan inspiration to become modern, then parse the estimated manufacturing costs. The design concept combines traditional and modern elements using a three-wheeled motorcycle to increase mobility and appeal to millennials. The method used is descriptive qualitative with data collection techniques through interviews, observations, and literature studies. The results showed that the modern angkringan cart based on a three-wheeled motorcycle has a minimalist, aesthetic, and efficient design. The materials used include hollow iron, aluminium plate, and wood to ensure durability. Red, yellow, and white colours were chosen to increase visual appeal and branding. The estimated cost of making the cart includes the cost of purchasing a motorcycle, materials, painting, accessories, labour services, as well as unexpected expenses, with a total budget of around IDR 50,500,000. This design offers high flexibility in mobility and operational efficiency. Further studies can evaluate the effectiveness of the design and maintenance over a period of time to improve the performance of modern angkringan carts.